Sustainable Landscape Construction: Materials and Products — Reduce, Reclaim, Reuse, Repurpose, Recycle, and Renew - Gail Hansen (EDIS, 2010)
ENH1140, a 1-page fact sheet by Gail Hansen, highlights several strategies that can be used in landscape construction to reduce resource use and protect the environment. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.